Numerical solution of first order stiff ordinary differential equations using fifth order block backward differentiation formulas - Nor Ain Azeany Mohd Nasir,; Zarina Bibi Ibrahim,; Khairil Iskandar Othman,; Mohamed Suleiman, (Universiti Kebangsaan Malaysia, 2012)
This paper describes the development of a two-point implicit code in the form of fifth order Block Backward Differentiation Formulas (BBDF(5)) for solving first order stiff Ordinary Differential Equations (ODEs). This method computes the approximate solutions at two points simultaneously within an equidistant block. Numerical results are presented to compare the efficiency of the developed BBDF(5) to the classical one-point Backward Differentiation Formulas (BDF). The results indicated that the BBDF(5) outperformed the BDF in terms of total number of steps, accuracy and computational time.